PENDIDIK DALAM PERSPEKTIF IIMAM AL GHAZALI DAN RELEVANSINYA DI ERA SOCIETY 5.0 - Moh Zaini; Noorthaibah Noorthaibah; Siti Julaiha (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The purpose of this research is to analyze the relevance of educators in the perspective of Imam al Ghazali in the era of society 5.0. Types of research in general, this study uses a library research model, derived from literary sources, whether in the form of books, manuscripts, journals. The Book of Ihya Ulumuddin. With a research focus on examining the Educator's Concept according to Imam al-Ghazali and its Relevance in the Era of Society 5.0. Primary data is the source of the material or documents presented. The primary data in this study is Ihya' Ulumuddin by Imam al-Ghazali. The results of research in the era of society 5.0 educators are very relevant to using complete and sophisticated and modern media such as computers, laptops equipped with educational media devices in the era of society are also equipped with very complete attributes and media that can help and guarantee the quality of educators as an educator in the era of society 5.0 which is actually also inseparable from technological developments. The role of educators in the era of society 5.0 as educators in the era of society 5.0. Abstrak Tujuan Penelitian ini adalah untuk menganalisis relevansi pendidik dalam perspektif Imam al Ghazali di era society 5.0. Jenis Penelitian secara umum, penelitian ini menggunakan model kepustakaan (library research), berasal dari sumber-sumber kepustakaan, baik berupa buku-buku, naskah, jurnal. Kitab Ihya ulumuddin. Dengan fokus penelitian untuk meneliti tentang Konsep Pendidik menurut Imam al- Ghazali dan Relevansinya di Era Society 5.0. Data primer adalah sumber bahan atau dokumen yang dikemukakan. Data primer pada kajian ini adalah Ihya’ Ulumuddin karya Imam al- Ghazali. Hasil penelitian di era society 5.0 pendidik sangat relevan dengan menggunakan media yang lengkap dan serba canggih dan modern seperti computer, laptop yang dilengkapi dengan perangkat media pendidik di era society juga dilengkapi oleh atribut dan media-media yang sangat lengkap yang bisa membantu dan menjamin kualitas pendidik tersebut sebagai seorang pendidik di era society 5.0 yang sebenarnya juga tidak lepas dari perkembangan teknologi Peran pendidik era society 5.0 sebagai pendidik di era society 5.0.